Pembrolizumab in patients with advanced upper tract urothelial carcinoma: a real-world study from ARON-2 project - Rizzo, Alessandro; Buti, Sebastiano; Giannatempo, Patrizia; Salah, Samer; Molina-Cerrillo, Javier; Massari, Francesco; Kopp, Ray Manneh; Fiala, Ondřej; Galli, Luca; Myint, Zin W; Tural, Deniz; Soares, Andrey; et al. (Clinical & experimental metastasis, 2024)
Upper tract urothelial carcinoma (UTUC) accounts for the 5-10% of all urothelial carcinomas (UCs). In this analysis, we reported the real-world data from the ARON-2 study (NCT05290038) on the efficacy of pembrolizumab in patients with UTUC who recurred or progressed after platinum-based chemotherapy. Medical records of patients with metastatic UTUC treated with pembrolizumab as second-line therapy were reviewed from 34 institutions in 14 countries. Patients were assessed for overall survival (OS), progression-free survival (PFS), and overall response rate (ORR). Univariate and multivariate analyses were used to explore the association of variables of interest with OS and PFS. 235 patients were included in our analysis. Median OS was 8.6 months (95% CI 6.6-12.1), the 1 year OS rate was 43% while the 2 years OS rate 29%. The median PFS was 5.1 months (95% CI 3.9-6.9); 46% of patients were alive at 6 months, 34% at 12 months and 25% at 24 months. According to RECIST 1.1, 18 patients (8%) experienced complete response (CR), 57 (24%) partial response (PR), 44 (19%) stable disease (SD), and 116 (49%) progressive disease (PD), with an ORR of 32%. Our study confirms the effectiveness of pembrolizumab in patients pretreated with a platinum-based combination, irrespective of their sensitivity to the first-line treatment and of their histology. In addition, we emphasized the limited benefit of the treatment with pembrolizumab in patients with hepatic metastases and poor ECOG performance status.
Keywords: Humans; Antineoplastic Agents, Immunological; Upper tract urothelial cancer; lidé středního věku; Pembrolizumab; karcinom z přechodných buněk; NCT05290038; urologické nádory; Female; Aged; dospělí; Survival; senioři; lidé; humanizované monoklonální protilátky; Immunotherapy; Urologic Neoplasms; Adult; Antibodies, Monoclonal, Humanized; ženské pohlaví; ARON-2 study; Male; Middle Aged; Retrospective Studies; Tumor response; Carcinoma, Transitional Cell; Aged, 80 and over; senioři nad 80 let; protinádorové látky imunologicky aktivní; retrospektivní studie; mužské pohlaví; Real-world data